Daniel Bryant, Lyric Poets of the Southern T'ang; Feng Yen-ssu, 903-960, and Li Yū, 937-978, Vancouver, University of British Columbia Press, 1982, lviii + 151 pp. - Maeth Ch., Russell (El Colegio de México, 1985)
-